Design of composite racing car body for student based competition - Salit, Mohd Sapuan; Ham, K. W.; Ng, K. M.; Woo, C. K.; Mohd Ariffin, Mohd Khairol Anuar; Baharudin, B. T. Hang Tuah; Abdul Aziz, Faieza; Supeni, Eris Elianddy; Abdul Jalil, Nawal Aswan (Academic Journals, 2009)
In this paper, total design method is used to develop a systematic route to design a car body fabricated by Faculty Engineering, University Putra Malaysia for competition and research purpose. A design of car body is implemented in this paper as a case study to enhance students understanding on developing a creative design. The design was carried out to meet the rules and regulation of “Formula Varsity UTeM 2008” competition organized by University Teknikal Malaysia (UTeM). The material selected in this car body design is carbon fiber reinforced polymer composite. The performance and reliability of the designed car body are considered by the means of engineering analysis, such as aerodynamic and stability.